THE INFLUENCE OF THE INDEPENDENT CURRICULUM ON THE PERCEPTION OF HISTORY TEACHERS IN LEARNING AT SENIOR HIGH SCHOOL NEGERI 1 TIBAWA - Kala, Kasma; Yunus, Resmiyati; Manay, Helman (Satmata: Journal of Historical Education Studies, 2024)
The Independent Learning Curriculum is one of the educational innovations introduced by the Ministry of Education, Research and Technology (Kemdikbudristek) to improve the quality of education in Indonesia. Tibawa 1 Public High School, as one of the educational institutions that implements the Independent Learning Curriculum, requires a deep understanding of history teachers' perceptions of this curriculum. The objectives of this research include, firstly, to determine the perceptions of history teachers regarding the independent learning curriculum at SMA Negeri 1 Tibawa. Second, find out what factors influence the policy regarding the conditions for independent study at SMA Negeri 1 Tibawa. The method used in this research is a qualitative method. The sources used come from interviews, observation and documentation.The results of the research show that, 1) The implementation of the Independent Learning Curriculum at SMA Negeri 1 Tibawa brought significant changes in the approach to learning history. The history teacher's view shows that the Merdeka Belajar Curriculum provides greater doctrine in curriculum preparation and implementation of learning. Teachers act as facilitators who guide and support students in a student-centered learning process; 2) Factors that influence the implementation of the Independent Learning Curriculum at SMA Negeri 1 Tibawa include the availability of resources and support from the school principal, teacher training and professional development, and student characteristics. Workshops and training have been held to ensure in-depth understanding and readiness of all relevant parties in implementing this curriculum.